Product Control Management Information System Using Eoq Method at Toko Herbamart - Jafar, Harun Al; Fauziah, Fauziah; Iskandar, Agus (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
This research focuses on product inventory management at Herbamart Store, a wholesale herbal medicine purchase center in South Jakarta. Currently, inventory control is done manually, which is not optimal and results in losses. The purpose of this research is to create a product inventory control management information system with the Economic Quantity Order (EOQ) method and a web-based application with an early warning system. The results showed that the optimal order quantity for various products can be determined by the EOQ method. The store also needs to provide safety stock and place a reorder when the remaining inventory reaches a certain amount. This research successfully designed a product control information system application using the web-based EOQ method tailored for Herbamart Stores. This application is designed to assist Herbamart Stores in optimizing their business processes, improving efficiency, and increasing profitability. This application can also help minimize the total cost of ordering and storing goods, thus contributing to reducing operational costs and improving overall efficiency. Keywords: Inventory Management, Economic Order Quantity (EOQ), Management Information System, Early Warning System, Toko Herbamart.